Demand management: the role of cross-functional integration in a context of political turbulence. Issue 3 (2nd March 2020) - Freitas, Marlos Rocha de; Pimenta, Márcio Lopes; Hilletofth, Per; Jugend, Daniel; Oprime, Pedro Carlos
Abstract : Purpose: The purpose of this study is to investigate how cross-functional integration supports the execution of the demand-side processes and its effects on both the demand and supply-side processes. Design/methodology/approach: A case study was conducted including a Brazilian multinational manufacturer in the automobile industry and some of its suppliers and dealers. 17 interviews were conducted. A theoretical framework is proposed containing five basic elements, they are: characteristics of the demand/supply processes; involved functions; integration factors; context influencers and impacts of integration on demand and supply processes. Findings: The findings present three demand-side processes (Product Launch, Marketing and Sales and Demand Planning) that demonstrated a greater need for cross-functional integration in the studied case, mainly through informal integration factors. Research limitations/implications: The empirical results of this study have methodological limitations due to the use of the case study method. Future research should analyze the effects of other context influencers (e.g. natural catastrophes, civil wars and low level of unemployment) on cross-functional integration. Practical implications: The results highlight that joint planning, willingness to work together, team spirit, adequate communication and cross-functional meetings helped the studied organizations to achieve competitive advantages and improve their performance. Originality/value: This study provides a theoretical framework that helped to improve the understanding of the interrelationships between demand management constructs and cross-functional integration factors. There are indications that a political–economic crisis has stimulated the existence of a willingness to work together and group spirit among employees who remain in the organization after mass dismissals. This climate of cooperation helped to increase the agility and resilience of the studied supply chain, which is currently affected by a changing market.